2016
DOI: 10.1192/bjp.bp.116.190165
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammatory and morphological changes in late-life depression: the NIMROD study

Abstract: We studied neuroinflammation in individuals with late-life depression, as a risk factor for dementia, using [11C]PK11195 positron emission tomography (PET). Five older participants with major depression and 13 controls underwent PET and multimodal 3T magnetic resonance imaging (MRI), with blood taken to measure C-reactive protein (CRP). We found significantly higher CRP levels in those with late-life depression and raised [11C]PK11195 binding compared with controls in brain regions associated with depression, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 13 publications
3
57
1
Order By: Relevance
“…According to one report, reduction in the volume of this area reflects a reduced density of the nerve cells themselves as well as glial cells . Another study has described the relationship between depression and inflammation, demonstrating microglial activity in sgACC, and suggested that neuroinflammation probably represents an important mechanism underlying the development of depression at an advanced age . Patients with depression show elevation of the serum levels of proinflammatory cytokines .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to one report, reduction in the volume of this area reflects a reduced density of the nerve cells themselves as well as glial cells . Another study has described the relationship between depression and inflammation, demonstrating microglial activity in sgACC, and suggested that neuroinflammation probably represents an important mechanism underlying the development of depression at an advanced age . Patients with depression show elevation of the serum levels of proinflammatory cytokines .…”
Section: Discussionmentioning
confidence: 99%
“…Significant codes; * P < 0.05, *** P < 0.001 inflammation, demonstrating microglial activity in sgACC, and suggested that neuroinflammation probably represents an important mechanism underlying the development of depression at an advanced age. 27 Patients with depression show elevation of the serum levels of proinflammatory cytokines. 28 We may infer that the microglia activated by stress induces the release of inflammatory cytokines within the brain and that these cytokines induce sustained activation of the sgACC, thereby injuring the glial cells of the sgACC.…”
Section: Figurementioning
confidence: 99%
“…Despite some negative results 6 , the majority of TSPO-PET studies in patients with depression have reported increased TSPO binding compared with healthy controls [7][8][9][10][11] , suggesting increased microglial activation in these patients. These studies thus propose that the inflammatory response in depression involves not only the periphery 12,13 but also the brain.…”
Section: Introductionmentioning
confidence: 98%
“…In general, females have higher rates of depression than males, especially older people with disabilities (Pagan-Rodriguez & Perez, 2012). Compared to older people without depression, older people with the diagnosis showed both central and peripheral signs of inflammation, and enhanced level of a specific translocator protein, which is associated with cardiovascular diseases (Su et al, 2016). Moreover, these patients showed significant gray matter reduction in the whole brain, which is associated with disruption of the neural network that regulates mood and behavior (Stratmann et al, 2014).…”
Section: Introductionmentioning
confidence: 99%